PENGARUH KOMBINASI IAA (Indole-3-Acetic Acid) DAN BAP (6-Benzylaminopurine) TERHADAP INISIASI TANAMAN VANILI (Vanilla planifolia Andrews) - Apri Salfiani; Asri Pirade Paserang (Biocelebes, 2021)
Provision of Vanilla (Vanilla planifolia Andrews) with traditional cultivation often has problems, including the availability of unhealthy seeds due to disease caused by Fusarium oxysporum. This disease can thwart vanilla plantations up to 85% because the pathogen can infect all parts of the vanilla plant making it difficult to control efforts. Alternative efforts were made to overcome this problem, namely through the initiation process in tissue culture by combining the hormones IAA (indole-3-acetic acid) and BAP (6-benzylaminopurine). This study aims to determine the effect and the maximum concentration of the combination of IAA and BAP on the initiation of vanilla plants. This study was conducted based on a completely randomized design (CRD) with 5 treatments and 3 repetitions. This treatment consisted of: A (MS + 0.1 ppm IAA + 1 ppm BAP), B (MS + 0.2 ppm IAA + 1 ppm BAP), C (MS + 0.3 ppm IAA + 1 ppm BAP), D (MS + 0.4 ppm IAA + 1 ppm BAP), and E (MS + 0.5 ppm IAA + 1 ppm BAP). Observations were made after 40 days from the planting process. The results showed that the concentration of the combination of IAA and BAP can affect the growth and organogenesis of the initiation of vanilla plants (Vanilla planifolia Andrews). Treatment C (MS + 0.3 ppm IAA + 1 ppm BAP) was the best concentration from this study, with average values: number of shoots (1), shoot length (1.73 cm), number of roots (1), and number of leaves (1.33).